Inorganic Frustrated Lewis Pairs in Photocatalytic CO2 Reduction. Issue 6 (18th February 2021) - Li, Taozhu; Zhang, Weining; Qin, Hao; Lu, Lei; Yan, Shicheng; Zou, Zhigang
Abstract: Carbon dioxide (CO2 ) conversion and utilization is a potential means to solve the energy crisis and environmental problems in modern times. However, the energy conversion efficiency is still limited by the high barriers in CO2 activation and conversion. Due to their ability to capture CO2, frustrated Lewis pairs (FLPs) have attracted much attention recently. In this Minireview, we first introduce the basic principles and challenges of photocatalytic CO2 reduction, including different CO2 reduction reaction pathways, product selectivity and water oxidation kinetics. Subsequently, research progress of FLPs on the activation of CO2 /H2 O molecules, charge separation and transfer and the product selectivity are discussed. Finally, the challenges in photocatalytic CO2 reduction are presented and future development directions are briefly described. Abstract : Frustrated Lewis pairs (FLPs) have attracted much attention recently due to their ability to capture carbon dioxide. This minireview introduces basic principles of photocatalytic CO2 reduction and subsequently discusses research progress on the applicated of FLPs on the activation of CO2 /H2 O molecules. Charge separation and transfer are also considered. (Image reproduced with permission from Appl. Catal. B 2021, 283, 119639, Copyright 2020 Elsevier).